Heat degradation of eukaryotic and bacterial DNA: an experimental model for paleomicrobiology - Nguyen-Hieu, Tung (BioMed Central, 2012)
BACKGROUND: Theoretical models suggest that DNA degradation would sharply limit the PCR-based detection of both eukaryotic and prokaryotic DNA within ancient specimens. However, the relative extent of decay of eukaryote and prokaryote DNA over time is a matter of debate. In this study, the murine macrophage cell line J774, alone or infected with Mycobacterium smegmatis bacteria, were killed after exposure to 90°C dry heat for intervals ranging from 1 to 48 h in order to compare eukaryotic cells, extracellular bacteria and intracellular bacteria. The sizes of the resulting mycobacterial rpoB and murine rpb2 homologous gene fragments were then determined by real-time PCR and fluorescent probing. FINDINGS: The cycle threshold (Ct) values of PCR-amplified DNA fragments from J774 cells and the M. smegmatis negative controls (without heat exposure) varied from 26–33 for the J774 rpb2 gene fragments and from 24–29 for M. smegmatis rpoB fragments. After 90°C dry heat incubation for up to 48 h, the Ct values of test samples increased relative to those of the controls for each amplicon size. For each dry heat exposure time, the Ct values of the 146-149-bp fragments were lower than those of 746-747-bp fragments. During the 4- to 24-h dry heat incubation, the non-infected J774 cell DNA was degraded into 597-bp rpb2 fragments. After 48 h, however, only 450-bp rpb2 fragments of both non-infected and infected J774 cells could be amplified. In contrast, the 746-bp rpoB fragments of M. smegmatis DNA could be amplified after the 48-h dry heat exposure in all experiments. Infected and non-infected J774 cell DNA was degraded more rapidly than M. smegmatis DNA after dry heat exposure (ANOVA test, p < 0.05). CONCLUSION: In this study, mycobacterial DNA was more resistant to dry-heat stress than eukaryotic DNA. Therefore, the detection of large, experimental, ancient mycobacterial DNA fragments is a suitable approach for paleomicrobiological studies.